Propagation of Taxus baccata Linn. by Stem Cuttings - Mitter, Harsh; Sharma, Anil (Indian Forester, 1999)
Taxus baccata Linn.growing in Dhauladhar Range is over exploited due to excessive collection of leaves for yield of anti-carcinogenic drugs like Taxol and Baccatin etc. The restoration and restocking of this II canopy tree under Q. semecarpifolia forests can be done through raising woody stem cuttings with growth regulators in February/July as the growth of seed raised plants is extremely slow. The experiments were carried out in the natural zone at forest nursery, Bir.